Problematics of Delegated Authority in Small-Scale Gold Mining Permit Issuance and Licensing Delays - Chairul A. M Tulie; Fenty U. Puluhulawa; Zamroni Abdussamad (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study analyzes the urgency of strengthening the authority of Regional Governments to issue Small-scale Gold Mining Permits within the framework of the relationship between the Central Government and Provincial Governments, as part of equitable licensing decentralization. Strengthening regional authority is essential to support regional autonomy and improve the effectiveness of natural resource management based on local conditions and community needs. This research employs a juridical-empirical method with a qualitative approach, examining mining regulations and a case study in Gorontalo Province. Primary data were collected through interviews with relevant stakeholders, while secondary data were obtained from legal literature, policy documents, and official publications. The findings show that the current delegated authority system creates administrative limitations and delays in permit issuance. Therefore, this study proposes strengthening provincial government authority through an attributive model to accelerate licensing services, enhance administrative effectiveness, and reinforce the regional role in accountable and sustainable mineral and coal mining governance.